The influence of effective microorganisms (EM) on the growth, production and egg quality of the commercial laying hen - Casey, N.H. (Norman Henry) (University of Pretoria, 2013)
Dissertation (MSc Agric (Nutritional Science))--University of Pretoria, 2006.